2020
DOI: 10.1101/2020.04.30.070011
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Barbadin selectively modulates FPR2-mediated neutrophil functions independent of receptor endocytosis

Abstract: Running title: Barbadin modulates specific neutrophil functions Abbreviations: Aoc = 2-aminooctanoic acid; AF = Alexa Fluor; AP2 = clathrin adaptor protein 2; AUC = area under the curve; BRET = bioluminescence resonance energy transfer; BSA = bovine serum albumin; CL = chemiluminescence; DMEM = Dulbecco's modified Eagle medium; DMSO = dimethyl sulfoxide; DPBS = Dulbecco's phosphate-buffered saline; FPR = formyl peptide receptor; GPCR = G protein-coupled receptor; HBSS = Hank's balanced salt solution; HRP = hor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…On the other hand, modifying the chemotaxis of neutrophils by regulating the internalization of GPCRs may improve the inflammatory response in the lungs during sepsis. Barbadin is a novel inhibitor that blocks the interaction of β-arrestin and AP-2, reducing receptor desensitization by inhibiting clathrin-mediated internalization of GPCRs, thus allowing neutrophils to continuously respond to external stimuli ( 325 , 326 ). Furthermore, LMBD1, the first protein was shown to be involved in the regulation of insulin receptor (IR) internalization ( 327 ), is hypothesized to contain nine transmembrane domains that subcellular localize in multiple membrane-bound organelles, including lysosomes and plasma membranes ( 328 ).…”
Section: Potential Therapeutic Targets For Septic Ardsmentioning
confidence: 99%
“…On the other hand, modifying the chemotaxis of neutrophils by regulating the internalization of GPCRs may improve the inflammatory response in the lungs during sepsis. Barbadin is a novel inhibitor that blocks the interaction of β-arrestin and AP-2, reducing receptor desensitization by inhibiting clathrin-mediated internalization of GPCRs, thus allowing neutrophils to continuously respond to external stimuli ( 325 , 326 ). Furthermore, LMBD1, the first protein was shown to be involved in the regulation of insulin receptor (IR) internalization ( 327 ), is hypothesized to contain nine transmembrane domains that subcellular localize in multiple membrane-bound organelles, including lysosomes and plasma membranes ( 328 ).…”
Section: Potential Therapeutic Targets For Septic Ardsmentioning
confidence: 99%
“…showed that the receptor down-stream signals generated by GPR84 reactivate FPR2 desensitized neutrophils also with this agonist which suggests that the reactivating signal(s) are generated independent of β-arrestin recruitment. The fact that also neutrophils activated/desensitized with FPR2 agonists unable to recruit β-arrestin (e.g., F2Pal10 and PSMα2) are reactivated by the receptor cross-talk signals generated by GPR84 (this study) as well as by the PAFR and P2Y2R (16)(17)(18)35), show that β-arrestin is not at all involved in the receptor cross-talk reactivation of FPR2. It would be highly interesting to explore the effect on neutrophil activation of a biased GPR84 agonist that is in favor of β-arrestin recruitment but to our knowledge, such a biased agonist has not yet been identified.…”
Section: Discussionmentioning
confidence: 66%
“…Recent research show that the signals generated by agonist occupied GPCRs differ depending on the agonist that initiates signaling, of which some, in addition to activating the heterotrimeric G protein, also may recruit β-arrestin to initiate non-canonical signaling (33). The FPR2 agonist F2Pal10 activates a Gi containing G-proteins but lacks the ability to recruit β-arrestin, and the signals downstream the activated receptor is thus biased (18,34,35). The data obtained using F2Pal10 as an FPR2 desensitizing agent clearly show that β-arrestin recruitment downstream FPR2 is not a feature that is required for the amplification the of GPR84 response.…”
Section: The Fpr2 Reactivation Signals Are Sensitive To Calyculin a Amentioning
confidence: 99%
“…Other FPR2 agonists, structurally unrelated to PSMα2, have earlier been shown to trigger a biased signaling/functional selective response (20,21,30,43). The concept of biased signaling applies also to FPR1 as illustrated by the results presented in a recent study, showing that signaling induced by the novel FPR1-selective small-molecule agonist RE-04-001 was strongly biased toward the PLC-PIP2-Ca 2+ and the ERK1/2 activation pathways, but away from β-arrestin recruitment (44).…”
Section: Discussionmentioning
confidence: 99%